2015
DOI: 10.1017/s1478951515000644
|View full text |Cite
|
Sign up to set email alerts
|

Older people with incurable cancer: Existential meaning-making from a life-span perspective

Abstract: The modified SOC model was seen as applicable for palliative care in specialized healthcare contexts. Employing the existential meaning-making framework with its complementary understanding of resilience as growth potential to the SOC model's restoration potential can help older people to identify how they make meaning and how this influences their adaptation process to being incurably sick.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…The experience of meaning in life has various definitions, many of which include the following three aspects: coherence, significance, and purpose (Martela & Steger, 2016;Park, 2010;Schnell, 2009). Generally, the experience of meaning in life changes during one's lifespan (Haug et al, 2016;Reker et al, 1987). Researchers have found that aging promotes the experience of meaning in life (e.g., Reker & Chamberlain, 2000;Schnell, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The experience of meaning in life has various definitions, many of which include the following three aspects: coherence, significance, and purpose (Martela & Steger, 2016;Park, 2010;Schnell, 2009). Generally, the experience of meaning in life changes during one's lifespan (Haug et al, 2016;Reker et al, 1987). Researchers have found that aging promotes the experience of meaning in life (e.g., Reker & Chamberlain, 2000;Schnell, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic events shatter one’s community and stable surroundings in which the individual’s meaning is embedded, which leads to a sense of meaninglessness, hopelessness, impotence, uncertainty, and lack of control in life. As mentioned by many existential psychologists and scholars, the threat evokes an existential exploration of what the most important things are in a person’s life and what he or she wants to live for [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observing how others confronted occupational performance challenges at the end of life provided practical alternate ways that could be tried. The process of attempted participation also afforded hope and quality of life and informed what was possible or not possible (Bates et al, 2018; Carter et al, 2004; Dunham et al, 2017; Ek & Ternestedt, 2008; Gulde et al, 2011; Jacques & Hasselkus, 2004; Johansson et al, 2006; Johnston et al, 2012; Kasven Gonzalez et al, 2010; Kjørven Haug et al, 2015, 2016; la Cour et al, 2007; la Cour & Hansen, 2012; Loughran et al, 2019; Malcolm et al, 2016; Mikkelsen et al, 2015; Olsson et al, 2010; Saarnio et al, 2016; Svidén et al, 2010; Turner et al, 2016; von Post & Wagman, 2019).…”
Section: Thematic Analysis Findingsmentioning
confidence: 99%